THE USE OF INNOVATIVE METHODS FOR FACING LOSS OF LEARNING AFTER THE COVID-19 PANDEMIC ERA FOR JUNIOR HIGH SCHOOL STUDENTS IN SUKOHARJO DISTRICT - Suyahman (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
Abstract. The purpose of this study is to Describe the use of innovative methods to deal with Learning Loss after the COVID-19 pandemic era for junior high school students in Sukoharjo Regency. This type of research is a qualitative research using case studies, the research subjects are seventh grade junior high school students in Sukoharjo Regency, and the object of the research is innovative methods and Learning Loss, data collection methods use: observation, interviews and documentation. The validity of the data using triangulation of methods and sources, data analysis techniques using interactive techniques consist of 3 stages: data reduction, data display and data verification. The results of the study show that the use of innovative methods is a must for all teachers in dealing with Learning Loss after the era of the covid 19 pandemic for junior high school students in Sukoharjo Regency. However, not all teachers have the ability to understand and apply innovative methods, so that there will be diversity in their use. The conclusions are: 1. Every teacher is obliged to use innovative methods in dealing with Learning Loss in the era of the covid 19 pandemic for junior high school students throughout Sukoharjo Regency, 2. The obstacles faced by teachers in using innovative methods are very complex because each teacher has different characteristics and abilities.Keywords: innovative methods and Learning Loss